ДЕЯКІ ОСОБЛИВОСТІ ЗАХИСТУ ІНТЕРЕСІВ СТОРІН ПРИ ЗАСТОСУВАННІ ІНСТИТУТУ ВІДНОВЛЕННЯ ПЛАТОСПРОМОЖНОСТІ - Aseeva, N.V. (Економіка та право, 2008)
The article analyzes some organizational-legal problems concerning prevention of bankruptcy and the mechanism for protection of economic subject's interests before legal proceedings in the procedure of bankruptcy as well as the protection of interests of a managing subject's employees. In order to provide efficient reorganization, resumption procedures and to protect the interests of the participants of procedure bankruptcy the following proposals have been offered to reorganize the Bankruptcy Agency into the State Fund for Bankruptcy with enlargement of competence; to change approach to preparation of arbitral managers; to form management commissions in the case of institution of an action against bankruptcy of a large enterprise headed by the Ministry of Economy of Ukraine or sectorial ministries.